Depot medroxyprogesterone and bone mineral density. Issue 1 (1st January 2002) - Ryan, P J; Singh, S P; Guillebaud, J
Abstract : Objective: To investigate depot medroxyprogesterone (DMPA)-associated bone loss in a general practice setting. Design: Forty-eight patients from a single practice who had used DMPA for contraception for more than 2 years. All patients had a serum oestradiol and if the serum level was <52 pmol/l or >52 pmol/l with menopausal symptoms, bone mineral densitometry (BMD) measurements were made at the lumbar spine (LS) and femoral neck (FN) using dual-energy x-ray absorptiometry (DEXA). Thirty-two patients had bone densitometry, of whom 27 had a serum oestradiol <52 pmol/l and five >52 pmol/l associated with menopausal symptoms. Of the remaining 16 patients, nine patients had a serum oestradiol <52 pmol/l but did not have a BMD as they moved away (five women) or switched to another contraceptive (four women). Results: BMD results showed a significantly reduced bone mass at both sites with mean Z score LS -0.84 (95% CI -1.17 to -0.52) and FN -0.32 (95% CI -0.62 to -0.02). Eighteen women (56% of 32 women) had either osteopenia (15 cases) (T score < -1.0) or osteoporosis (three cases) (T score < -2.5) at the LS. There were trends to an association of a family history of height loss or tobacco smoking (current or past) for LS and FN Z scores that did not quite achieve significance. There was also a trend to lower body weight in those with a possible family history of osteoporosis or who were smokers and an inverse correlation of weight with BMD at the FN (p < 0.05) and a non-significant inverse correlation at the LS. Conclusion: The present results demonstrate that a low bone mass should be considered in patients with prolonged DMPA usage especially if they have risk factors for osteoporosis.